Ekonomi Digital dan Hukum Ekonomi Syariah: E-Commerce, Aset Digital dan Implikasi Hukumnya Menurut Hukum Islam - Ikhsan, Muh; Sapa, Nasrullah bin; Syatar, Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The development of digital technology has brought significant changes in the economic field. One of them is the emergence of new transaction models in the world of economics, such as e-commerce, cryptocurrencies and other digital assets. This journal aims to analyze the digital economy from the perspective of Islamic economic law with a focus on the legality of e-commerce transactions and ownership of digital assets. By using a normative approach and literature study, this journal tries to highlight critically-contextually the importance of strengthening Islamic (economic) principles in the digital ecosystem with the aim that transactions carried out based on the digital economic platform do not conflict with Islamic values (teachings) manifested in the concept of Islamic economics. The results of this study indicate that digital economic transactions can be permitted in Islam as long as the working system meets the pillars and conditions of the contract in Islamic economics and is free from elements of usury, gharar and maisir.